Heart rate recovery and diastolic blood pressure ratio on the treadmill test predict an induction and recurrence of vasovagal syncope - Choi, Yu Jeong; Kang, Ki-Woon; Jang, Sang Hyun; Kim, Jae Guk; Lee, Soo Joo; Jung, Kyung Tea (The Korean journal of internal medicine, 2019)
The induction and recurrence of syncope is a concerning situation that could be unpredicted in the vasovagal syncope (VVS). We investigated a simple predictor for the induced and recurrent VVS during Head-Up table-tilt Test (HUT) and clinically follow-up. The 143 consecutive patients with VVS (age 31 ± 19 years, 33 male) who referred by a cardiologist or neurologist and had undergone an echocardiogram, HUT, and a treadmill exercise test (TMT) were recruited and clinically follow-up. Patients were divided into two groups based on the result of HUT and TMT. The data was analyzed and compared between VVS patients and control 141 patients without VVS who were enrolled in the same study period (age 40 ± 5 years, 117 male). The heart rate recovery (HRR), recovery systolic blood pressure (RecSBP), recovery diastolic blood pressure (RecDBP), HRR/RecSBP and HRR/RecDBP were significantly different between controls and VVS during the TMT. Within VVS, even if, baseline characteristics were similar between negative and positive HUT (n = 92 vs. n = 51). HRR (31 ± 10 vs. 35 ± 10), HRR/RecSBP (0.24 ± 0.09 vs. 0.28 ± 0.09) and HRR/RecDBP (0.49 ± 0.18 vs. 0.58 ± 0.19) were significantly different between negative and positive HUT results. Especially, HRR/RecSBP and HRR/RecDBP were significantly correlated with induced syncope with a sensitivity and specificity ([60%, 83%] cut-off, 0.31; [72%, 80%] cut-off, 0.63). In the Cox regression, HRR/ RecDBP were significantly associated with recurrence of VVS with hazard ratio of 3.29 (confidence interval, 0.95 to 11.3; p = 0.049). HRR/RecDBP may be a useful predictor for induction during HUT and recurrence during follow-up in the VVS.